The Heterogenation Of Saccharin, Melamine And Sulfonic Acid Onto Rice Husk Ash Silica And Their Catalytic Activity In Esterification Reaction - Hello, Kasim Mohammed (2010)

(untitled)
Sodium silicate from rice husk ash (RHA) was functionalized with 3– (chloropropyl)triethoxysilane (CPTES), 3–(mercaptopropyl)trimethoxysilane and 3–(aminopropyl)triethoxysilane to give RHACCl, RHAPrSH and RHAPrNH2 via a simple one–pot synthesis. The 29Si MAS NMR of RHACCl showed the presence of T2, T3, Q3 and Q4 silicon centres, while the T1, T2, T3, Q2, Q3 and Q4 silicon centres were present in both RHAPrSH and RHAPrNH2. The 13C MAS NMR showed that RHACCl had three chemical shifts at 10.37, 26.70 and 47.69 ppm, which was attributed to the three carbon atoms of the CPTES moiety